The Impact of Islamic Religious Education on Students' Spiritual and Social Development: A Study at Universitas Muhammadiyah Semarang - Imron, Ali; Mamdukh Budiman; Budi Setyono; Mardian Hayati; Safril Ahamdi Sanmas (LPPM Universitas PGRI Semarang, 2025)
In the era of globalization, students are expected to possess intellectual, spiritual, and social intelligence. Spiritual, and social intelligence to navigate complex societal challenges effectively. However, the role of Islamic Religious Education (PAI) in fostering these qualities, particularly in higher education, remains underexplored. This study examines the impact of PAI on students' spiritual and social qualities. This study bridges this gap by examining the effects of PAI on students' spiritual and social qualities. This study examines the impact of Islamic Religious Education (PAI) on improving students' spiritual and social qualities at the Faculty of Agricultural Science and Technology, University Muhammadiyah Semarang. The research employed a quantitative survey method using accidental sampling, involving 150 third-semester students who had completed the PAI course. Data were collected through a 12-item questionnaire and analyzed using descriptive analysis and t-tests. The results indicate that PAI learning significantly enhances students' spiritual quality, reflected in their understanding of religious teachings, frequency of worship, and ethical awareness. Social quality also showed significant improvement, as evidenced by increased participation in social activities, empathy towards others, and effective communication skills. All variables demonstrated a p-value of less than 0.05, indicating significant changes after the PAI learning. Although this study highlights the crucial role of PAI in shaping students' character, it has several limitations, such as its single-faculty focus, reliance on a specific questionnaire, and short-term observation, highlight the need for further research. Moreover, the study only observed short-term effects, suggesting the need for further research with